Finnish and Swedish NATO membership: A path towards more regional security or instability? - Filipović Aleksa (Srpska Politička Misao)
With the ascension of both Finland and Sweden to NATO, the Scandinavian and Baltic regions are facing the restructuring of the security architecture that can lead either toward more regional security or instability. This research aims to identify potential points of conflict between NATO and Russia that can develop after Finland and Sweden joined NATO, and to give an assessment of the possibility of military escalation between Russia and NATO. This is achieved by employing content analysis during the research of the reports, strategies, and doctrines, as well as with employment of the case-study method, which was used when analyzing specific examples of the interaction between the Nordic countries, NATO, and Russia in the Scandinavian and Baltic regions. With three potential regional conflict points between NATO and Russia identified, which are the Baltic Sea/Kaliningrad, the Russo-Finnish border, and the Arctic region, it can be concluded that Finnish and Swedish NATO membership applications, as well as their ascension to NATO, are a cause for the increase of the conflict potential in the region, which can lead towards NATO-Russia military escalation and probable employment of nuclear weapons.